Millennials' Consumer Behavior in the Coffee Agroindustry: The Effect of Consumer Attitudes on Purchasing Decisions - Dyah Ismoyowati; Shafira Wuryandani; Fadhila Kurnia Wijayanti (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
Enjoying a good cup of coffee is gaining popularity among Indonesian millennials, particularly in metropolitan areas, with an annual growth rate of 6% in the last decade. Therefore, this study aimed to provide information for adjusting coffee shop marketing strategies by estimating the influence of consumer attitudes, in particular, motivation and perception, and lifestyle, on their purchasing decisions. We sampled 153 individuals (majorly aged 25 to 27 years, with a slight bias toward females) in Yogyakarta, Java, using an online survey with 33 questions on consumer attitudes, along with four demographic questions. The responses were converted to a Likert score and analyzed using multiple linear regression. Our results demonstrate that the consumer attitudes investigated collectively explained 41%, with motivation and perception being the dominant factor (F = 51,401 ; p < 0.05). It showed that motivation and perception, and lifestyle variables significantly affected coffee shop purchasing decisions among millennials in Yogyakarta. At the same time, the F test revealed that they had a combined effect significantly. Therefore, coffee shop owners must consider consumers' motivation and perception, and lifestyle to increase millennial coffee shop consumers' loyalty in Yogyakarta.